Exploring the role of Islam on the lived experience of patients with Long QT Syndrome in Saudi Arabia. Issue 4 (22nd February 2022) - Bakur, Khadijah H.; Al‐Aama, Jumana Y.; Alhassnan, Zuhair N.; Brooks, Helen; Clancy, Tara; Manea, Waleed; Takroni, Saud A.; Ulph, Fiona
Abstract: Genetic services are rapidly growing in the Arab world leading to increasing number of patients being diagnosed with genetic disorders. Islam is the only/major religion of the local population in these countries. Muslim patients integrate religion in virtually every aspect of their lives, and it is vital to understand the role of Islam on their coping and decision‐making in the context of genetic counseling. This will help provide patients with the most appropriate services aligned to their religious beliefs and will improve outcomes. Increasing numbers of patients are being diagnosed with Long QT syndrome in Saudi Arabia. Using semi‐structured interviews, this study explored the role of Islam on the lived experience of 13 Saudi participants diagnosed with autosomal dominant Long QT syndrome (3/13) or who are carriers of Jervell and Lange‐Nielsen syndrome (10/13). The interviews investigated how they made sense of living with the condition in light of their religion/spirituality. The data were analyzed using interpretative phenomenological analysis and produced four superordinate themes: 1) Common belief and idiosyncratic interpretation; 2) Using religion to justify positive reframing of current illnesses; 3) Interplay between belief in medicine and in religion; and 4) Complex impact of diagnosis on religiosity. The results show that the participants' idiosyncratic interpretations of the religious principles, not the principles themselves, had an important influence on their coping, medical decision‐making, perceptions regarding the cause of their disease, and compliance with medical advice. A novel insight of the current study is that the personal understanding and interpretation of medical information played the greatest role in the decision‐making process, and not the religious beliefs. Thus, it is important for health professionals to give patients' information in a manner that is clear and detailed in order for them to facilitate an informed decision, and to ensure that they fully understand the implications.